Pengaruh Double Chamfer terhadap Distribusi Suhu dan Daerah Zpl pada Sambungan Las Gesek AL6061 dengan Simulasi Komputer - Nadya, Mesti; Irawan, Yudy Surya; Choiron, Moch. Agus (Jurnal Rekayasa Mesin, 2021)
Welding is one of the metal joining processes in manufacturing. CDFW (continuous drive friction welding) is a welding process to join two workpieces by applying pressure at one end of the object and rotating another one where the friction action applies at interface. The purpose of this study is to study temperature distribution on the surface of the welding area and the heat-affected zone represented by a fully plasticized zone (Zpl) and to get an insight of a friction welding process. The variables of CDFW used were double chamfer angle, upset pressure, and burn off  length. The initial area of friction was equal that is at a diameter of 14 mm. The method of modeling the CDFW friction welding is via computer simulations using ANSYS 18.1 software. This research uses aluminum material type Al6061. The Taguchi method was applied in designing the simulations. In this modeling, the model with the double chamfer of 15 °, the upset pressure of 120 MPa, and the burn-off length of 9 mm has a small ZPl area of 10.256 mm2. Whilst the specimen model, with a double chamfer angle of 45 °, the upset pressure of 240 MPa,   and the burn-off length of 7 mm has a large Zpl area of 56.55mm2. The area of a narrow fully plasticized area caused by small chamfer angle and an upset pressure of 240 MPa. The area of fully plasticized zone shows how much material can be integrated during the friction welding process and how much strength of the weld metal. The model with the chamfer angle of 15 º,   the upset pressure of 240 MPa, and the burn-off length of 9 mm has the widest temperature distribution and the highest maximum temperature. Meanwhile, the model with the chamfer angle of 30º, the upset pressure of 120 MPa, and the burn-off length of 9 mm has the narrowest temperature distribution and the lowest maximum temperature. The smaller chamfer angle increased upset pressure and burn-off length result in the wider temperature distribution, higher maximum temperature, and smaller Zpl.